2017
DOI: 10.1128/aem.01239-17
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Multimeric Proteins via Intersubunit Cyclization

Abstract: Proteins with high catalytic efficiency and selectivity under mild conditions have long been appreciated by industrial and medicinal fields. These proteins, which are commonly multimeric, often possess low stability, impeding wider application. Currently, strategies to improve the stability of multimeric proteins concentrate on enhancing the interaction at internal interface of the subunits. In this report, we confirmed that the largely underestimated subunit terminal ends are as significant as the internal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In S. equi subsp . zooepidemicus ATCC35246, 5'-Nucleotidase (5NuC) was found to directly degrade the NET DNA backbone to deoxyadenosine, negatively influencing macrophage phagocytic activity, while the mutant strain Δ5nuc exhibited lower virulence and a weaker ability to spread from blood to organs than the WT strain (Ma et al 2017 ).Similar findings were reported in S. pyogenes for 5'-nucleotidase A (S5nA)(Zheng et al 2015 ). Therefore, our results are in agreement those of previous studies showing SsSTK mutant strains displayed reduced ability to adhere to epithelial cells, increased immune evasion and increased sensitivity to phagocytosis (Zhu et al 2014 ; Zhang et al 2017 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In S. equi subsp . zooepidemicus ATCC35246, 5'-Nucleotidase (5NuC) was found to directly degrade the NET DNA backbone to deoxyadenosine, negatively influencing macrophage phagocytic activity, while the mutant strain Δ5nuc exhibited lower virulence and a weaker ability to spread from blood to organs than the WT strain (Ma et al 2017 ).Similar findings were reported in S. pyogenes for 5'-nucleotidase A (S5nA)(Zheng et al 2015 ). Therefore, our results are in agreement those of previous studies showing SsSTK mutant strains displayed reduced ability to adhere to epithelial cells, increased immune evasion and increased sensitivity to phagocytosis (Zhu et al 2014 ; Zhang et al 2017 ).…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, the putative IgA-specific zinc metalloproteinase (ZmpC or IgA1) (Zhang et al 2011 ; Dumesnil et al 2018 ), translation initiation factor 2 (HP0272 or SadP) (Ferrando et al 2017 ), chaperone protein DnaJ (Zhang et al 2015 ), and sensor histidine kinase TCS VarS (Zheng et al 2018a ; Zhong et al 2018 ) were significantly up-regulated in the mutant strain. Another 43 VFs that have been reported in other pathogens were identified as DEPs in the ∆stk , including putative 5'-nucleotidase (5NuC) (Zheng et al 2015 ; Ma et al 2017 ), trypsin-like serine protease (HtrA) (Backert et al 2018 ) and metalloendopeptidas (PepO) (Agarwal et al 2013 , 2014 ). These VFs were mainly assigned into eight classes: (i) amino acid transport and metabolism (12 proteins); (ii) posttranslational modification, protein turnover, chaperones (10 proteins); (iii) nucleotide transport and metabolism (9 proteins); (iv) transcription (8 proteins); (v) inorganic ion transport and metabolism (6 proteins); (vi) cell wall/membrane/envelope biogenesis (6 proteins); (vii) general function prediction (3 proteins); and (viii) other proteins of unknown function (7 proteins) (Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…2). Tetrameric configurations are reported most often and likely represent the majority of SDR protein structures in solution [43].…”
Section: Discussionmentioning
confidence: 99%
“…[15] Like many other multimeric proteins, [16] ADHs have a natural tendency to dissociate their subunits, leading to rapid inactivation. [17] Thus, prevention of their disassociation is the priority for stabilizing these interesting enzymes. In our previous study, we identified a highly capable ADH (LnADH) from Leifsonia.…”
mentioning
confidence: 99%
“…In our previous study, we identified a highly capable ADH (LnADH) from Leifsonia. [17] LnADH is able to use NADH as a cofactor rather than the more expensive NADPH. Moreover, it is able to use the solvent isopropanol to recycle the generation of NADH, thus significantly reducing the cost and improving the solubility of substrates.…”
mentioning
confidence: 99%